Jump-starting America : how breakthrough science can revive economic growth and the American dream - Gruber, Jonathan; Johnson, Simon, 1963- (PublicAffairs, 2019)
The untold story of how America once created the most successful economy the world has ever seen and how we can do it again. - publisher's website.